A modern choice for patients with hypertension: the possibility of new calcium antagonist of III generation - E. I. Emelina; G. E. Gendlin (Рациональная фармакотерапия в кардиологии)
Features and possibility of application of the calcium channel blocker lercanidipine in cardiology practice are discussed. The use of lercanidipine in patients with hypertension is supported by extensive evidences. The use of lercanidipine in certain categories of patients, including patients receiving combination therapy is also considered. The safety of lercanidipine in cardiac patients is discussed separately.